Clinicopathological characteristics and rituximab addition to cytotoxic therapies in patients with rheumatoid arthritis and methotrexate‐associated large B lymphoproliferative disorders. Issue 1 (5th February 2015) - Yamada, Kozue; Oshiro, Yumi; Okamura, Seiichi; Fujisaki, Tomoaki; Kondo, Seiji; Nakayama, Yoshifuku; Suematsu, Eiichi; Tamura, Kazuo; Takeshita, Morishige
<x xml:space="preserve">Abstract</x> Aims To analyse the clinicopathological characteristics and prognosis of 40 rheumatoid arthritis (RA) patients with methotrexate (MTX)‐associated large B cell lymphoproliferative disorders (MTX–BLPD). Methods and results Soluble interleukin 2 receptor titres (median 1500 U/ml) in 40 patients with MTX–BLPD were lower than those of 24 RA patients with non‐MTX‐ associated (non‐MTX) BLPD (5731 U/ml) and 15 with control diffuse large B cell lymphoma (DLBCL, 5918 U/ml) (P < 0.01). Using in‐situ hybridization, Epstein–Barr virus (EBV) was detected in tumour cells of 25 of 40 RA patients with MTX–BLPD (63%). Immunohistologically, BCL2 expression was detected in 35% of patients with MTX–BLPD, which was lower than 93% of control DLBCL patients (P < 0.01). Eleven patients with EBV+ MTX–BLPD (44%) showed remission after MTX withdrawal. In RA patients with clinical stage III/IV BLPD, 15 with rituximab (R)+ cytotoxic therapies pursued better prognosis than 10 with R− cytotoxic therapies (P < 0.05). Among the 15 patients, seven with MTX–BLPD showed better overall survival than nine control DLBCL patients (P < 0.01). Conclusions In RA patients with MTX–BLPD, immunosuppression by MTX, EBV infection and low BCL2 expression in tumour cells may play roles in tumorigenesis and tumour regression. R+ cytotoxic therapies as well as MTX withdrawal were highly effective in these patients.